2023
DOI: 10.1097/shk.0000000000002169
|View full text |Cite
|
Sign up to set email alerts
|

Circtdrd9 Contributes to Sepsis-Induced Acute Lung Injury by Enhancing the Expression of Rab10 via Directly Binding to Mir-223-3p

Rui Zhang,
Xiaoyan Dang,
Jie Liu
et al.

Abstract: Background The dysregulation of circular RNAs (circRNAs) is involved in various human diseases, including sepsis-induced acute lung injury (ALI). We aimed to investigate the role of circTDRD9 in the development of sepsis-induced ALI. Methods Cell models of sepsis-induced ALI were established by treating A549 cells with LPS. The expression of circTDRD9, miR-223-3p and RAB10 mRNA was measured by quantitative real-time PCR (qPCR). The levels of inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The role of these proteins in ferroptosis-induced ALI should be confirmed in the future. In addition, although we analyzed miRNAs targeting key genes, miRNAs also involved in the occurrence of ALI (48), we did not predict the lncRNAs related to the upstream regulation of miRNAs. miRNA expression is influenced by upstream molecules such as lncRNAs, which can also serve as targets for disease treatment and diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…The role of these proteins in ferroptosis-induced ALI should be confirmed in the future. In addition, although we analyzed miRNAs targeting key genes, miRNAs also involved in the occurrence of ALI (48), we did not predict the lncRNAs related to the upstream regulation of miRNAs. miRNA expression is influenced by upstream molecules such as lncRNAs, which can also serve as targets for disease treatment and diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…The increased HECTD1 protein expression is associated with macrophage activation and contributing to the progression of silicosis ( Fang et al, 2018 ; Zhou et al, 2018 ). It is found that circRNA11:120406118|12040782 was increased in the peripheral serum of silicosis patients, which facilitated the progress of silicosis by aggravating NLRP3-mediated macrophages pyroptosis through sponging miR-30b-5p ( Zhang et al, 2023 ).…”
Section: Circrnas In Inhalation Lung Injurymentioning
confidence: 99%